Association between life satisfaction, sleep disturbance and mental health problems among the migrant older adults with children: a conditional process analysis based on per capita bedroom area - Mingli Pang; Jieru Wang; Hexian Li; Guangwen Liu; Xiaoxu Jiang; Jing Xu; Shixue Li; Fanlei Kong (BMC Geriatrics)
Abstract Background The relationship between life satisfaction and mental health problems had been confirmed in many existed studies, but the underlying mediating and moderating effect of sleep disturbance and per capita bedroom area (PCBA) behind this association had never been identified. This study aimed to explore the mediating role of sleep disturbance and the moderating effect of PCBA on the association between life satisfaction and mental health problems. Methods Multistage cluster random sampling method was used to select the participants and finally 613 migrant older adults with children (MOAC) were included in the survey. A conditional process model was performed to examine the relationship between life satisfaction and mental health problems, as well as the mediating effect of sleep disturbance and the moderating effect of PCBA. Results Life satisfaction was negatively associated with mental health problems, and sleep disturbance could mediate their association. Furthermore, the direct effect of life satisfaction on mental health problems and the indirect effect of sleep disturbance in the relationship were moderated by PCBA, but it only moderated the direct effect and the second indirect link (sleep disturbance-mental health problems) of the mediating effect. Both these two effects were stronger for MOAC with a low level of PCBA. Conclusions Life satisfaction had negative effect on mental health problems. PCBA moderated the direct effect of life satisfaction on mental health problems and the mediating effect of sleep disturbance on mental health problems. For MOAC with a low level of life satisfaction and high sleep disturbance, particularly those with a low level of PCBA, targeted implication for the community, family members and MOAC were proposed to improve the mental health of MOAC.